2019
DOI: 10.21276/ijcmr.2019.6.5.49
|View full text |Cite
|
Sign up to set email alerts
|

Study of Colistin Sensitivity Pattern of Pseudomonas Aeruginosa in a Tertiary Care Hospital

Abstract: Pseudomonas is an invasive organism that causes severe Hospital Acquired Infections in immune compromised hosts and it exhibits a high degree of resistance to broad spectrum antibiotics. In recent years Colistin is the drug of choice for use against MDR strains. The aim was to study the antibiotic susceptibility and Colistin sensitivity pattern of Pseudomonas isolates from various samples. Material and methods: 100 Pseudomonas aeruginosa isolates from various samples (exudates, bloods and urines) were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Pseudomonas auerogenosa 34 63 Pseudomonas aueroginosa to colistin. Pseudomonas aueroginosa sensitivity to Carbapenems was much lower than colistin (10.3%), in study of Ramalakshmi discussed previously, the sensitivity was 67% [17]. The possible explanation is the wide spread use of Carbapenems on empirical basis which led to high resistance.…”
Section: Organisms Frequency Percentmentioning
confidence: 88%
See 1 more Smart Citation
“…Pseudomonas auerogenosa 34 63 Pseudomonas aueroginosa to colistin. Pseudomonas aueroginosa sensitivity to Carbapenems was much lower than colistin (10.3%), in study of Ramalakshmi discussed previously, the sensitivity was 67% [17]. The possible explanation is the wide spread use of Carbapenems on empirical basis which led to high resistance.…”
Section: Organisms Frequency Percentmentioning
confidence: 88%
“…Pseudomonas aueroginosa was sensitive to colistin in 79.3% cases, while in a study conducted in china Zhang H et al, found a sensitivity of 94.6% [16] and Ramalakshmi et al detected sensitivity of 83% [17]. Somily AM found 93 % Pseudomonas aueroginosa sensitive to colistin [18].…”
Section: Discussionmentioning
confidence: 99%